Time trends in leisure time physical activity, smoking, alcohol consumption and body mass index in Danish adults with and without COPD - Hansen, Henrik (BMC Pulm Med, 2016)
BACKGROUND: Promotion of a healthy lifestyle and non-pharmacological interventions in the treatment of chronic obstructive pulmonary disease (COPD) has received great attention in recent decades. The aim of this study was to investigate trends in leisure time physical activity (PA), smoking, alcohol consumption and body mass index (BMI) from 2000 to 2010 in Danish individuals with and without COPD. METHODS: Analyses were based on data provided by The Danish Health and Morbidity’s three cross-sectional surveys from 2000, 2005 and 2010. Data compromised level of leisure time PA, smoking, alcohol consumption, BMI and sociodemographic characteristics. Participants aged 25 years or older with and without COPD were included in the analyses. RESULTS: In multiple logistic regression analyses, odds ratio (OR) of being physically active in the leisure time in 2010 compared to 2000 was 1.70 (95 % CI: 1.28-2.26), p < 0.001, and 1.32 (1.22-1.43), p < 0.001, in participants with and without COPD, respectively. Being a non-smoker in 2010 compared to 2000 was associated with an OR of 1.41 (1.07-1.85), p = 0.015, and 1.73 (1.63-1.85), p < 0.001, in participants with and without COPD. The OR of not exceeding national recommended alcohol limits was 0.64 (0.45-0.93), p = 0.020, and 1.19 (1.09-1.29), p < 0.001, in participants with and without COPD. In a multiple linear regression analysis, the time frame from 2000 to 2010 was associated with an increased BMI of 1.18 kg · m(−2) (0.52-1.84), p < 0.001, and 0.74 kg · m(−2) (0.63-0.86), p < 0.001, in participants with and without COPD. The COPD participants with higher levels of education and/or living in a marriage or a relationship were more likely to be physically active, non-smoking and not exceeding the recommended alcohol limits. CONCLUSION: From the 2000 to 2010, Danish individuals aged 25 years with and without COPD, increased their leisure time PA level and reduced smoking. Lower socioeconomic status was associated with a reduced level of PA, smoking and an increased alcohol intake. Future national health campaigns and treatment strategies need to target this socioeconomic impact. The reported increased PA level and reduced smoking may have important implications in relation to a reduced morbidity and mortality risk in Danish patients with COPD.